2002
DOI: 10.1053/jhep.2002.36160
|View full text |Cite
|
Sign up to set email alerts
|

PI3K-FRAP/mTOR pathway is critical for hepatocyte proliferation whereas MEK/ERK supports both proliferation and survival

Abstract: Growth factors are known to favor both proliferation and survival of hepatocytes. In this work, we investigated the role of 2 main signaling pathways, phosphoinositide 3-kinase (PI3K) and mitogen-activated protein kinase (MEK)/extracellular signal-regulated kinase (ERK), in these processes. First, evidence was provided that the PI3K cascade as well as the MEK/ERK cascade is a key transduction pathway controlling hepatocyte proliferation, as ascertained by arrest of DNA synthesis in the presence of LY294002, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
100
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 42 publications
13
100
1
1
Order By: Relevance
“…We have recently shown that AR can induce the synthesis of DNA in isolated hepatocytes through the activation of the EGF-R (31), and our current in vitro experiments show that the activation of the EGF-R by AR is also necessary to convey its antiapoptotic effect. The ability to induce cellular proliferation is often correlated with the promotion of survival (24), and the downstream PI3K, ERK1/2, and STAT3 pathways have been shown to be major regulators of cell proliferation and survival in response to growth factors (24,(43)(44)(45)(46)(47)57). Our data indicate that the antiapoptotic activity of AR on Fas-mediated cell death is independent of the ERK1/2 pathway but dependent of PI3K.…”
Section: Discussionmentioning
confidence: 63%
“…We have recently shown that AR can induce the synthesis of DNA in isolated hepatocytes through the activation of the EGF-R (31), and our current in vitro experiments show that the activation of the EGF-R by AR is also necessary to convey its antiapoptotic effect. The ability to induce cellular proliferation is often correlated with the promotion of survival (24), and the downstream PI3K, ERK1/2, and STAT3 pathways have been shown to be major regulators of cell proliferation and survival in response to growth factors (24,(43)(44)(45)(46)(47)57). Our data indicate that the antiapoptotic activity of AR on Fas-mediated cell death is independent of the ERK1/2 pathway but dependent of PI3K.…”
Section: Discussionmentioning
confidence: 63%
“…[16][17][18] Activated ERK1 and ERK2 serine (S)/T kinases phosphorylate and activate a variety of substrates. [19][20][21][22][23][24][25] 90 kDa ribosomal six kinase 1 (p90 Rsk1 ) is one such substrate. p90 Rsk1 can activate the cyclic-AMP response element-binding protein (CREB) transcription factor.…”
Section: Overview Of the Ras/raf/mek/erk Pathwaymentioning
confidence: 99%
“…Consistent with the above finding that EGFR is necessary for A 1 R-induced neuroprotection, the involvement of Akt activation in EGFR transactivation by A 1 R stimulation was supported by finding a concentrationdependent inhibition of these responses after pretreatment with EGFR kinase inhibitor AG1478. The activation of RTKs, such as EGFR and PDGFR, often triggers the recruitment of PI3K and the activation of Akt [20] . We pretreated cortical neurons with the selective PI3K inhibitor wortmannin (Wort, 100 nmol/L, 30 min) and then stimulated with CPA (1 μmol/L, 5 min).…”
Section: Egfr Transactivation Mediated By a 1 R Stimulation Is Dependmentioning
confidence: 99%